2010
DOI: 10.1002/ps.2032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fungicide resistance and pathogen diversity in Erysiphe necator using quantitative real‐time PCR assays

Abstract: The real-time PCR assay developed in this study provides a potentially useful tool for efficient quantification of different alleles of interest for fungicide monitoring and for population structure of E. necator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 45 publications
1
52
0
1
Order By: Relevance
“…However, it has been suggested that such chemical fungicides represent a potential risk to the environment and to human health, with the additional problem of generating fungal resistance (Bardas et al. 2010; Dufour et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that such chemical fungicides represent a potential risk to the environment and to human health, with the additional problem of generating fungal resistance (Bardas et al. 2010; Dufour et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance phenotype of these isolates was not determined, but in a separate study, 17 out of 18 isolates with Y136F had higher resistance factors (median RF = 27) to one or more DMIs than all isolates lacking the mutation (median RF = 1) (L. Rallos, un published data). The occurrence of double resistance to DMI and Qol in E. necator was earlier reported in Europe (14), and DMIresistant isolates of Monilinia fructicola have been found to be predisposed to accelerated development of Qol resistance (mech anism not investigated) (32). These phenomena can limit the use of DMIs and Qols as rotational or tank mix partners.…”
Section: Discussionmentioning
confidence: 93%
“…; Dufour et al . ) and (ii) the developed assay is based on genetic differences between alleles of the Avr3a gene, the proposed quantitative diagnostic tool can be efficiently used to screen virulent and avirulent natural P. infestans populations.…”
Section: Introductionmentioning
confidence: 99%